How the Domain Name Scruffles are Rocking the Foundations of Trade Mark law - Keane, Rachel (Victoria University of Wellington Law Review, 2001)
The central proposition of this paper is that it is no longer valid to assert that the only and proper function of the trade is to denote the source of the product to which it is affixed. Trade marks are being employed in many diverse ways. In the age of mass media, trade marks may provide the key to marketing successfully. The dilution doctrine has developed in recognition of the potential value of a trade mark to tis owner. Anti-dilution provisions, as far as they go, do provide a useful tool in protecting the trade mark itself. However, as technology continues to advance, so does the trade mark function. The so-called domain name disputes, primarily in the United States are evidence of this claim. Not only have the decisions in these cases furthered the development of the trade mark legislation, they have demonstrated the inadequacies of the current trade mark legislation and the desperate need for reform. These inadequacies are examined and reform is proposed. Finally, the paper assesses the desirability of allowing the further expansion of the trade mark. It is submitted that the proper expansion of the trade mark should not be resisted.